Nakazawaea Atacamensis F.A., Sp. Nov. a Novel Nonconventional Fermentative Ascomycetous Yeast Species from the Atacama Desert - Cubillos-Riffo, F; Villarreal-Diaz, P; Araya, M; Urbina, K; Del Pino, J (John Wiley and Sons Ltd, 2024)
In this study, we describe Nakazawaea atacamensis f. a., sp. nov., a novel species obtained from Neltuma chilensis plant samples in Chile s hyperarid Atacama Desert. In total, three strains of N. atacamensis were obtained from independent N. chilensis samples (synonym Prosopis chilensis, Algarrobo). Two strains were obtained from bark samples, while the third strain was obtained from bark-exuded gum from another tree. The novel species was defined using molecular characteristics and subsequently characterized with respect to morphological, physiological, and biochemical properties. A neighbor-joining analysis using the sequences of the D1/D2 domains of the large subunit ribosomal RNA gene revealed that N. atacamensis clustered with Nakazawaea pomicola. The sequence of N. atacamensis differed from closely related species by 1.3%–5.2% in the D1/D2 domains. A phylogenomic analysis based on single-nucleotide polymorphism s data confirms that the novel species belongs to the genus Nakazawaea, where N. atacamensis clustered with N. peltata. Phenotypic comparisons demonstrated that N. atacamensis exhibited distinct carbon assimilation patterns compared to its related species. Genome sequencing of the strain ATA-11A-BT revealed a genome size of approximately 12.4 Mbp, similar to other Nakazawaea species, with 5116 protein-coding genes annotated using InterProScan. In addition, N. atacamensis exhibited the capacity to ferment synthetic wine must, representing a potential new yeast for mono or co-culture wine fermentations. This comprehensive study expands our understanding of the genus Nakazawaea and highlights the ecological and industrial potential of N. atacamensis in fermentation processes. The holotype of N. atacamensis sp. nov. is CBS 18375T. The Mycobank number is MB 849680. © 2023 John Wiley & Sons Ltd.
Keywords: Atacama; fermentation; novel species; yeast